Bilocular unicystic ameloblastoma of the mandible in a 9 yr old child – A diagnostic and management dilemma - Faisal Al Sineedi; Yasin Alavi Aruveetil; Abdul Majeed Kavarodi; Shawqi Osman Harbi (Saudi Dental Journal)
Unicystic ameloblastoma is a less encountered variant of the ameloblastoma that usually presented as unicystic lesions of jaw occurring in 3rd and 4th decades of life. It shows a typical ameloblastomatous epithelium lining the cyst cavity, with or without variable tumor proliferations. The case presented here is of a 9 yr old boy who was referred to our center for the management of a large diffuse swelling on the right side of the face. Clinical and radiologic evaluation showed two interconnected cystic lesions in the right body and the symphyseal regions of the mandible associated with impacted canines bilaterally. The initial histopathology of both cystic spaces showed the lesion to be dentigerous cysts and the results were reconfirmed in two other centers. A complete surgical enucleation of this bilocular cyst was done sparing the impacted teeth. The histopathologic examination of the post-operative specimen showed features of Unicystic Ameloblastoma. The patient was followed up on a regular basis for more than 3 years. There is no signs of recurrence and his latest radiographic examinations shows good bone formation. The impacted teeth are erupting into position. This case reports the difficulty in clinical diagnosis and the peculiar bilocular presentation of unicystic ameloblastoma which was conservatively managed by surgical enucleation of the complete lesion, sparing the dentition. Keywords: Unicystic ameloblastoma, Dentigerous cyst, Keratocystic odontogenic tumour, Plexiform ameloblastoma, Enucleation